Evolutionary and functional divergence of Sfx, a plasmid-encoded H-NS homolog, underlies the regulation of IncX plasmid conjugation - Avril Wang; Martha Cordova; William Wiley Navarre (mBio)
ABSTRACT Conjugative plasmids are widespread among prokaryotes, highlighting their evolutionary success. Conjugation systems on most natural plasmids are repressed by default. The negative regulation of F-plasmid conjugation is partially mediated by the chromosomal nucleoid-structuring protein (H-NS). Recent bioinformatic analyses have revealed that plasmid-encoded H-NS homologs are widespread and exhibit high sequence diversity. However, the functional roles of most of these homologs and the selective forces driving their phylogenetic diversification remain unclear. In this study, we characterized the functionality and evolution of Sfx, a H-NS homolog encoded by the model IncX2 plasmid R6K. We demonstrate that Sfx, but not chromosomal H-NS, can repress R6K conjugation. Notably, we find evidence of positive selection acting on the ancestral Sfx lineage. Positively selected sites are located in the dimerization, oligomerization, and DNA-binding interfaces, many of which contribute to R6K repression activity—indicating that adaptive evolution drove the functional divergence of Sfx. We additionally show that Sfx can physically interact with various chromosomally encoded proteins, including H-NS, StpA, and Hha. Hha enhances the ability of Sfx to regulate R6K conjugation, suggesting that Sfx retained functionally important interactions with chromosomal silencing proteins. Surprisingly, the loss of Sfx does not negatively affect the stability or dissemination of R6K in laboratory conditions, reflecting the complexity of selective pressures favoring conjugation repression. Overall, our study sheds light on the functional and evolutionary divergence of a plasmid-borne H-NS-like protein, highlighting how these loosely specific DNA-binding proteins evolved to specifically regulate different plasmid functions.IMPORTANCEConjugative plasmids play a crucial role in spreading antimicrobial resistance and virulence genes. Most natural conjugative plasmids conjugate only under specific conditions. Therefore, studying the molecular mechanisms underlying conjugation regulation is essential for understanding antimicrobial resistance and pathogen evolution. In this study, we characterized the conjugation regulation of the model IncX plasmid R6K. We discovered that Sfx, a H-NS homolog carried by the plasmid, represses conjugation. Molecular evolutionary analyses combined with gain-of-function experiments indicate that positive selection underlies the conjugation repression activity of Sfx. Additionally, we demonstrate that the loss of Sfx does not adversely affect R6K maintenance under laboratory conditions, suggesting additional selective forces favoring Sfx carriage. Overall, this work underscores the impact of protein diversification on plasmid biology, enhancing our understanding of how molecular evolution affects broader plasmid ecology.